Computational simulation for identification, evaluation and relocation of pregnant women in a possible zika infection outbreak in South American cities - Nieto Chaupis, Huber (2016)
We use computational simulation to identify, evaluate and relocate pregnant women in a possible scenario of attack of Zika virus (ZIKV) on Peri-urban zones of South American cities. The plausibility of this study is based on the following points: (i) existence of high population of pregnant women in Peri-urban areas of large cities, (ii) appropriate conditions for fast reproduction of Aedes aegypti mosquitoes along hills, and (iii) the potential association of the ZIKV infection to microcephaly in babies. By assuming an attack rate of 15 per 1000 habitants as well as rate of confirmation of 10 cases per day, and rapid intervention based on the displacements of pregnant women to cleaned areas, the simulation yields that at least 2±1 of 100 pregnant women might be infected by ZIKV. The simulations have emphasized the effect of applying rapid intervention expected to be done by the health specialists, that targets to identify as soon as possible all those women in situation of pregnancy few hours after the presence of Aedes is already confirmed.